An unusual cause of exertional dyspnea in a 55 years old man. (2020) - Vézina, Félix-Antoine; Milad, Daniel; Godbout, Krystelle; Bernier, Mélanie; Maltais, François; Nadreau, Éric; Sénéchal, Mario
Abstract: A 55-year-old former professional athlete reported out of proportion dyspnea on exertion. After a detailed cardiac investigation, a cardiopulmonary exercise test on an ergocycle demonstrated an abnormal and non-physiological ventilatory response characterized by a sharp rise in ventilation followed by a decrease while exercise workload was progressively increasing. This was accompanied by noisy breathing. A laryngoscopy with direct visualisation of larynx and vocal cord during voluntary eucapnic hyperventilation confirmed the diagnosis of exercise-induced laryngeal obstruction. The patient was treated with speech therapy and all the symptoms resolved. A second cardiopulmonary exercise test showed a normalisation of the ventilatory pattern during exercise. This case demonstrates the importance of recognizing the symptoms of an exercise-induced laryngeal obstruction regardless of age, and the effectiveness of the speech therapy on symptoms and on exercise testing.